SENYAWA GOLONGAN FLAVONOID PADA EKSTRAK n-BUTANOL KULIT BATANG BUNGUR (Lagerstroemia speciosa Pers.) - I. A. R. Astiti Asih; I M. Adi Setiawan (Jurnal Kimia (Journal of Chemistry), 2008)
Isolation and identification of flavonoid compounds from skin of Bungur (Lagerstroemia speciosa Pers.)have been conducted. Isolation was carried out by maceration and partition, to obtain n-hexane, ethyl-acetate, and nbutanolextracts. Concentrated n-butanol extract was purified using thin layer chromatography and columnchromatography.Isolate F2.6 from n-butanol extract contains flavonoid compounds. Uilta Violete - Visible spectra showedthat the flavonoid compounds were flavanon or dihidroflavanol, with characteristic wavelengths from 275 to 295 nmfor Band II and 350 to 400 nm for Band I. Shifting reagents added indicated no hydroxyl group at C-3 and C-5,hydroxyl group at C-7, no ortho-dihydroxyl group at ring A,B, or C, and O-glycoside at C-7. Infrared spectraindicated characteristic functional groups of O-H bonded, CH alifatic, C=O, C=C aromatic, C-O, and CH aromatic.The flavonoid compounds indicated was flavanon group, which has functional groups of O-H bonded, CHalifatic, C=O, C=C aromatic, C-O, and CH aromatic, and hydroxyl group at C-7. It does not have ortho-dihydroxylgroup at ring A,B, or C, but has O-glycoside at C-7.